Zayed University, United Arab Emirates: Adult Educators as Midwives of Emiratization - K. Kathleen O'Neill (Adult Education Research Conference, 2008)
The purpose of the study is to identify the business communications skills entry-level managers in Abu Dhabi, United Arab Emirates need and to use this to inform program development in order to promote emiratization.
Keywords: emiratization; United Arab Emirates; employment; business communication